ANALYSIS OF DIFFERENCES BETWEEN MALE AND FEMALE STUDENTS IN THE EAT26 EATING HABITS ASSESSMENT TEST - Ivana Ćosić Mulahasanović,; Amra Nožinović-Mujanović,; Edin Mujanović,; Alem Šabović,; Ivan Ledić,; Anđelko Šimić, (Sport Scientific And Practical Aspects, 2025)
The paper emphasizes that the period of beginning study is alarming, because through the new life circumstances, obligations and environment, great changes occur and a personal hierarchy of values and priorities of students in their lives is formed. The aim of the research was to determine eating habits and differences in relation to gender among students at the University of Tuzla. The research was conducted on a sample of 813 respondents, male and female students of the University of Tuzla. Eating attitude test (EAT26) is used for diagnosis of eating habits. Obtained results sowed statistically significant difference between male and female students in the applied test EAT26.